Resource intensity trends of ferrochrome production in South Africa - Dlamini, Reuben Mkhuleko (Department of Chemical Engineering, 2021)
South Africa owns more than 70% of the world's known chromite reserves. Chromite has historically been the most feasible source of chromium suitable for ferrochrome production, which in turn is an essential raw material for stainless steel production. Stainless steel has a myriad of applications in modern society. The South African ferrochrome industry was developed on the foundation of abundant raw material; historically cheap electricity and labour; and investment into industry research and infrastructure. The industry, like other mineral industries, has made a significant contribution to the socio-economic development of South Africa. The South African government, through the Department of Mineral Resources, has drafted a mineral beneficiation strategy that is focused on developing the downstream industry to leverage the abundant mineral resource for prolonged and increased benefit to the South Africa. Yet while the ferrochrome and stainless-steel value chains have been identified as strategic, their mining and processing is resource intensive and a significant contributor to emissions that have the potential of causing environmental degradation. In order to have meaningful engagement between stakeholders, there must be reliable information. This has resulted in the development of sustainability indicators to facilitate engagement. Of the various types of sustainability indicators, resource intensity, which is the ratio of the resource used to the unit product, was selected for this study. This was because resource intensity trends can be used to show the effects of environmental constraints quantitatively and qualitatively, such as ore grade and the effects of technological innovation on processing a mineral resource. In this way, decisions can be made regarding the environmental impacts and the technology required to mitigate these. From a review of similar studies, it was found that approach for a similar included gathering data from mining company reports and, where possible, collaborating with companies. These data were then compiled to identify trends showing whether industries have improved in certain aspects. The causes of those variations were also reported in conjunction with the trends. In certain instances, expert insights were used to support the investigations. Most studies found that ore grades gradually decline, which increases input into the industry. However, technology improvements and improved process improvements have the potential to mitigate the effects of these declining ore grades. This observation informed the development of the hypothesis for this study, which is that process and technology improvements could avert an increase in resource input when an ore grade declines. The methodology adopted for this study included compiling resource intensity trends from publicly available sources over the period 2007-2017 (and on one occasion data were shared by a ferrochrome producing company), mapping major industry projects over this period, and conducting interviews with eight industry experts to verify trends and establish the impact of technology choice in relation to observed resource intensity trends. It was assumed that the quality of the data was uniform and of a sufficiently high quality for comparison and analysis. Although ore grade trends could not be obtained, it was inferred that ore grade is decreasing. This is due to increased usage of Upper Group 2 (UG2) seam chromium concentrate, which has a lower grade than the conventional higher ore grade, Lower Group 6 (LG6), or Middle Group 1 and 2 (MG1/2) seam ore. Moreover, the chrome source raw material quality used in ferrochrome production was found to be improving with the advent of pelletising and sintering technology, which makes it possible to use UG2 ore. This technology increases the durability of the ore, which also improves the efficiencies. This has led to the development of industrial symbiosis, whereby platinum group metal (PGM) producers generate UG2 tailings, which are sent to co-located ferrochrome producers to produce chromium concentrate. Chromium concentrate forms part of the raw material to produce sintered pellets which are used to produce ferrochrome. Electricity intensity was also observed to decrease over time due to improvements in process energy integration. The increased application of closed furnaces allows the use of flue gas from smelting for combustion to generate electricity and heat transfer of the hot gas to be used to heat up other process streams. The addition of a prereduction increased energy efficiency, in addition to improving ore efficiencies, collectively reduced the electricity requirements. Furthermore, the increased use of chrome sintered pellets has contributed to the decline in electricity intensity. Water intensity trends could not be conclusively determined due to evolving water accounting. It was inferred that if the water accounting remained constant from when it was reported to change, the water intensity was also decreasing. This has been attributed to increased water efficiency investments such as increased paving of water canals to increase recycling. Reductant intensities could not be confirmed as there were insufficient data to draw the trends and consequently review them. It was mentioned that new Glencore proprietary furnace technology has reduced the requirement of expensive coke reductant. The impetus of most of these projects was remaining profitable. The continual increase in the price of electricity in South Africa has propelled ferrochrome producers to reduce their electricity usage, as electricity accounts for up to 50% of ferrochrome production costs (Pan, 2013). Legal compliance has also motivated some technology implementations. For instance, in preparation for the carbon tax, manufacturers reduced their electricity use and started to increase the combustion of carbon monoxide off-gas from smelting for electricity production and other applications such as heat integration and prereduction. There has also been an increase in awareness of climate change and greenhouse gases, and the need for more responsible and sustainable mineral processing. The public perception of a company can significantly affect its profitability, with environmental protests affecting operations and consequently profits.